(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: Water plays an important role in human life, animals, plants and other bodies. The water we need is water that meets the requirements of good health, physical requirements, chemical, bacteriological and radioactive. Uncontaminated water is defined as water that does not contain a specific foreign substances in quantities exceeding the limits set so that the water can be used normally. General conditions faced Water District Kawangkoan North in connection with customer service that is the difficulty in installation or connection to a public that has been registered but has not been connected or has not received installation, as well as the distribution of water that sometimes substandard home-home customer. As for the purpose of this study was to determine how the effectiveness of local water companies in North Minahasa District Kawangkoan. The method of this research is qualitative research methods and data collection techniques in this study is the observation / observation localized research, conduct interviews, and documentation. The research shows that there are some constraints in the service of the Regional Water Company office in North Kawangkoan. Keywords: Effectiveness Service, the Regional Water Company.